The Role of Machine Learning in Digital Forensics - Qadir, Abdalbasit Mohammed; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2020)
Digital forensics, as a branch of the forensic sciences, is facing new challenges from the aspect that potential digital evidence is growing and expanding. Rapid development in the fields of computer science and information technology provides innovative techniques for digital investigations. In this paper, the important role of machine learning is explained as an application of artificial intelligence, and how it can be used to analyse large amounts of diverse datasets in order to reveal any criminal behaviour and intent through learning from previous and historical activities to predict criminal behaviours in the future. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: Computer Science; Digital Forensics; Forensic Sciences; Machine Learning